The pharmacokinetics of ceftazidime in lactating and non-lactating cows - Rule, R. (1996)
The pharmacokinetics of ceftazidime (CAZ) were studied in lactating (LTG) and non-lactating (NLTG) cows. Two groups (LTG and NLTG) of 5 healthy dairy cows were given ceftazidime (10 mg/ kg body weight) intravenously (i.v.) and intramuscularly (i.m.). Serum and milk (LTG) and serum samples (NLTG) were collected over a 24-h period post-administration. CAZ concentrations in serum and milk were determined by high-performance liquid chromatography, and an interactive and weighted-non-linear least-squares regression analysis was used to perform the pharmacokinetic analysis. The pharmacokinetic profiles in LTG and NLTG cows which had received CAZ i.v. fitted a three-compartment model and a two-compartment model, respectively. The CAZ concentration-time curves in serum and the area under the curve were greater and more sustained (p<0.05) in the LTG cows by both routes, while the serum clearance (Cls=72.5±18.1 ml/h per kg) was lower (p<0.05) than that in the NLTG cows (Cls=185.9±44.2 ml/h per kg). CAZ given i.v. exhibited a relatively long half-life of elimination (t; 1/2 β (LTG)=1.1±0.2 h; t; 1/2 β (NLTG)=1.4±0.3 h). Compared with other cephalosporins, CAZ had good penetration into the mammary gland (47.7±38.2% for CAZ i.v.; 51.1±39.0% for CAZ i.m.). Finally, the bioavailability of CAZ (F(LTG)=98.9±36.8%; F(NLTG)=77.1±25.3%) was suitable for its use by the i.m. route in lactating and non-lactating cows.